Data warehousing and business intelligence for e-Commerce - Simon, Alan R.; Shaffer, Steven L. (San Francisco : Morgan Kaufmann, 2001)
You go online to buy a digital camera. Soon, you realize you've bought a more expensive camera than intended, along with extra batteries, charger, and graphics software-all at the prompting of the retailer. Happy with your purchases? The retailer certainly is, and if you are too, you both can be said to be the beneficiaries of "customer intimacy" achieved through the transformation of data collected during this visit or stored from previous visits into real business intelligence that can be exercised in real time. Data Warehousing and Business Intelligence for e-Commerce is a practical exploration of the technological innovations through which traditional data warehousing is brought to bear on this and other less modest e-commerce applications, such as those at work in B2B, G2C, B2G, and B2E models. The authors examine the core technologies and commercial products in use today, providing a nuts-and-bolts understanding of how you can deploy customer and product data in ways that meet the unique requirements of the online marketplace-particularly if you are part of a brick-and-mortar company with specific online aspirations. In so doing, they build a powerful case for investment in and aggressive development of these approaches, which are likely to separate winners from losers as e-commerce grows and matures. * Includes the latest from successful data warehousing consultants whose work has encouraged the field's new focus on e-commerce. * Presents information that is written for both consultants and practitioners in companies of all sizes. * Emphasizes the special needs and opportunities of traditional brick-and-mortar businesses that are going online or participating in B2B supply chains or e-marketplaces. * Explains how long-standing assumptions about data warehousing have to be rethought in light of emerging business models that depend on customer intimacy. * Provides advice on maintaining data quality and integrity in environments marked by extensive customer self-input. * Advocates careful planning that will help both old economy and new economy companies develop long-lived and successful e-commerce strategies. * Focuses on data warehousing for emerging e-commerce areas such as e-government and B2E environments.
Part I: Foundations: Concepts and Business Models -- Chapter 1: Background, Terminology, Opportunity, and Challenges -- Chapter 2: Business-to-Consumer Data Warehousing -- Chapter 3: Data Warehousing for Consumer-to-Consumer and Consumer-to-Business Models -- Chapter 4: Business-to-Business Data Warehousing -- Chapter 5: e-Government and Data Warehousing -- Chapter 6: Business-to-Employee Models and Data Warehousing -- Part II: Building Blocks, Challenges, and Solutions -- Chapter 7: Core Technologies and Building Blocks -- Chapter 8: Products for e-Commerce Intelligence -- Chapter 9: Data Quality and Integrity Issues -- Chapter 10: Information Privacy and Systems Security Issues for e-Commerce Environments -- Chapter 11: Solutions Architecture Case Study.
Includes index.
Keywords: Electronic commerce; Business intelligence; Data warehousing; Industrial marketing; Electronic books